Diseño de un sistema unidirecional satelital para difusión de datos en la escuela rural Pedro Cornelio Drouet. - Segura Medranda, Héctor Miguel (2022)
This project aims to provide an alternative for Internet access to rural school students who do not have this indispensable resource through the design and analysis of a VSAT network, ideal for non-served isolated villages or rural areas that use regional public networks. Relevant statistical data is also presented, showing these rural educational institutions' bleak access to technological resources and services. The second chapter describes the different elements that make up the network, the most used architectures and frequency bands, multiple access protocols, and the main current applications. It also studies satellite communications' characteristics, advantages, disadvantages, and elements. In the third chapter, the design methodology is established, a mathematical analysis of the radiofrequency link from the satellite to the earth station is performed, and the main parameters of both the earth stations and the space segment must be known when performing the calculations that characterize the performance of the link are defined. A procedure to be followed when dimensioning the bandwidth occupied by a VSAT network is developed. A detailed description is given of how to calculate the radio frequency link between a remote station and the satellite transponder. On the other hand, use the "Satellite Communications Toolbox" of MATLAB for verifying and validating the calculations performed manually. The results of the radiofrequency link provide the necessary data to determine the feasibility and viability, as well as the calculation of the bandwidth required when implementing a VSAT network.